FORMULAS! SELAI PISANG RAJA BULU DENGAN TEMPE DAN DAYA SIMPANNYA - Dian Sundari; Komari Komari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
Background: Jelly or jam is preserved foods, typically made from fruit by adding sugar or concentrated dektrosa with total dissolved solids content of at least 65%. Factors to consider in making butter, among others, temperature and sugar content of pectin and citric acid. Some aspects include the type of pectin, acid type and quality of fruit used and the cooking and filling procedures can also impact on the quality of butter, good physical stability and microorganisms. Methods: The addition of tempe in a jam aims to improve the nutritional value of vegetable protein. The study covers the development of formulations of jam, jelly organoleptic test to determine who was elected and also chemical analysis such as protein content, ash content and total sugar content as well as microbiological testing TPC to save power jam. Results: The results showed that the organoleptic test of banana jam and tempe is jam treatment A with the addition of citric acid: pectin = 0.5%: 1%. Results of chemical analysis of the average protein content of 6.1%, an average ash content of 1.80% and average total sugar content 35.57%. During the storage up to week-3, the jam has an average water content of 25.31%- 26.25%; pH range from 5 to 6.15; aw values ranged from 0.75 to 0.83 and the average TPC 1.6 x 102 to 2.2 x 103. From the microbiological test, jam-elect still worth consumed up to week-1 because his total number of microbes that is 4.7 x 102 is still below the maximum limit TPC jam by SNI (5 x 102 colonies / gram).   Keywords: formulation, nutrition, quality, jam, bananas, tempe